Peamaclein – A new peach allergenic protein: similarities, differences and misleading features compared to Pru p 3. Issue 1 (24th December 2012) - Tuppo, L.; Alessandri, C.; Pomponi, D.; Picone, D.; Tamburrini, M.; Ferrara, R.; Petriccione, M.; Mangone, I.; Palazzo, P.; Liso, M.; Giangrieco, I.; Crescenzo, R.; et al.
Summary Background Among the peach‐derived allergens which are already known, the lipid transfer protein (Pru p 3) seems to be the one to exert severe allergic reactions. Objective To identify and characterize a new peach allergen causing a clinical picture similar to that of Pru p 3. Methods Patients were selected on the basis of their severe clinical reactivity and negative results to a panel of peach allergens available on the ISAC103 microarray. Several in‐house and commercial preparations were compared. Several methods were used to characterize the newly identified molecule. Specific IgE and inhibition assays were performed using the Allergen micro‐Beads Array (ABA) assay. Results Negative ISAC results to Pru p 3 were confirmed by additional testing in contrast with the positive results obtained by commercial Pru p 3‐enriched peach peel extracts. The analyses of one of these preparations led to the identification of Peamaclein, a new allergenic protein. It is a small, basic, cysteine‐rich, heat‐stable, digestion‐resistant protein, homologous to a potato antimicrobial peptide. Peamaclein was able to trigger positive skin test reactions and to bind IgE in the ABA assay. It displays an electrophoretic mobility and chromatographic behaviour similar to that of Pru p 3; therefore, it can be hidden in Pru p 3 preparations. In fact, Pru p 3‐enriched peach peel extracts were found to contain both Pru p 3 and Peamaclein by means of comparative in vivo testing, and by biochemical and immunochemical assays. Commercially available anti‐Pru p 3 polyclonal antibodies were found to have a double specificity for the two molecules. Conclusions and Clinical Relevance A new allergen from peach belonging to a new family of allergenic proteins has been identified and characterized. This knowledge on Peamaclein will improve our understanding on the clinical aspects of the peach allergy and the quality of diagnostic reagents.